A Prospective Randomized Crossover Study in Single Sided Deafness on the New Non-Invasive Adhesive Bone Conduction Hearing System. Issue 8 (September 2018) - Mertens, Griet; Gilles, Annick; Bouzegta, Rajae; Van de Heyning, Paul
Abstract : Background: Recently, an adhesive bone conduction hearing system has been developed for conductive hearing loss or single-sided deafness (SSD). In SSD cases, this device may be a good solution for patients who are unsuitable for, or who do not wish to undergo, bone conduction implant or cochlear implant surgery. The study aimed to investigate the hearing outcomes with the adhesive hearing system in SSD. Purpose of the Study: The study aimed to investigate the hearing outcomes with the adhesive hearing system in SSD. Methods: A randomized crossover study was conducted in 17 SSD participants, using CROS (contralateral routing of signals) hearing aid as a control. Following outcome measurements were administered after a two-week trial: 1) Speech, Spatial and Qualities scale, Audio Processor Satisfaction Questionnaire, and a custom-made questionnaire about the use of the system, 2) sound localization, 3) speech perception in noise. Results: 70% of the SSD subjects reported that the adhesive hearing system was partially useful or better. Using the APSQ, the adhesive test device was evaluated equally as the control device. Sound localization improved with the adhesive test device and deteriorated with the control device. There was no improvement in speech perception in noise measured with the adhesive test device. Speech perception in noise (SSSD NNH ) with the control device improved significantly. Conclusion: To the best of our knowledge, this is the first study to report on the outcomes of the new adhesive system. Users' satisfaction of the adhesive hearing system was found to be comparable to the control device. Since the hearing outcomes vary highly between patients, trials with applicable hearing systems are recommended in SSD patients.